Neue Ergebnisse der Karsthydrologie: Untersuchungen im Dachsteingebiet mit Hilfe der Sporentriftmethode - Zötl, Josef G. (ERDKUNDE, 1957)
Since 1954 the author has been carrying out karst hydrographic investigations in the south-eastern Dachstein area (Upper Austrian — Styrian Limestone Alps). The Dachstein massif is a typical representative of cast Alpine block shaped mountains; thick layers of Triassic limestones and dolomites which lie on top of marly Werfen strata and Paleozoic phyllites rise steeply from the surrounding valleys. The massif possesses extensive plateau surfaces with pronounced karst features and lacks surface drainage. In order to clarify the catchment areas of the foreland streams, in the summer of 1956, spores of Lycododium clavatum were put into five sink holes on the plateau of the eastern Dachstein area and springs at the foot of the massif were kept under observation with plancton nets. This spore drift method, which was introduced in 1953 by A. Mayr for the investigation of a subterranean watercourse in the western Dachstein area, proved its worth also in this case. This method has the advantage that in contrast to the usual method of putting chloride or dyes into karst streams, the amount of material and the number of people required can be very small, a fact which may be of decisive importance for investigations in out of the way and not easily accessible places. This spore drift method was further developed in the eastern Dachstein area by using dyed spores. The results of the five experiments which were carried out in the eastern Dachstein area lead to the conclusion that there is an interconnected and water filled network of cavities, a karst water system, whose culmination lies in the central part of the Massif. Practical results of these investigations were that they allowed conclusions to be reached for the calculation of the catchment areas of the foreland streams in limestone mountains and also as regards the problems of preventing the pollution of springs. In addition conclusions could be drawn about the subterranean drainage of block shaped Alpine limestone mountains. In this respect the concept of A. Grand (1903, 1910) that there is a uniform karst water table in limestone mountains opposed the theory of O. Lehmann (1932) according to which the subterranean drainage of a limestone massif takes place by means of a number of independent karst vessels. The results of the spore drift experiments in the eastern Dachstein area brought these two contrasting theories into closer proximity; although it was possible to prove the existence of an on the whole interconnected karst water system, the possibility of a complete transfer of the concept of the characteristics of ground water in loose permeable rock to the conditions in limestone mountains does, however, not exist. The validity of the results gained by the spore drift experiments in the eastern Dachstein area must for the time being, of course, be limited to karst massifs in the eastern Alps, until the results of further investigations elsewhere become available.